Pelatihan Promosi Dan Pemasaran Produk UMKM MACO Melalui Media Sosial Di Desa Padang Birik-Birik Kota Pariaman - Rinaldi; Rusli, Devi; Cut Sarha Airlangga; Ibnu Hatta Ramadhan; Ali Arben (PUSAKO : Jurnal Pengabdian Psikologi, 2023)
UMKM partners consist of several young business actors who are still studying/undergraduates who come from various educational backgrounds. Their motivation for entrepreneurship is mostly due to economic demands. They learn business autodidactically, relying more on their knowledge and experience in developing their business. As a result, their UMKM production has not experienced significant progress, so far it has only been to meet daily needs. Currently, business development in the digital era requires strategies in promotion and marketing. Business actors must have digital promotional technology and product marketing skills in order to compete. Some partner UMKM business units have promoted and marketed their products on social media and e-commerce, but this has not been done consistently. This community service aims to increase the literacy and skills of UMKM business actors in promoting UMKM products in the e-commerce marketplace and on social media via live streaming. Community service activities have opened partners' insight into the importance of promoting UMKM products in online media. Partners also gain experience marketing UMKM products via live streaming on social media. . Keywords: Training, Promotion, Micro, Small and Medium Enterprises